Analisis Rentabilitas untuk Mengukur Kinerja Keuangan pada Koperasi Pegawai Republik Indonesia Universitas Negeri Makassar - Pertiwi, Nabilah; Natsir, Uhud Darmawan; Anwar; Tawe, Amiruddin; Nurman (MES Management Journal, 2024)
A cooperative is a group, in which there is various collaborations exist to achieve common goals. The nature of the cooperative itself is a business, which is based on the principles of the people's economic movement and the principle of kinship. Profitability is an indicator for assessing the financial performance of an organization, in this case the Republic of Indonesia Employee Cooperative, Makassar State University (KPRI UNM). This research aims to determine the level of profitability of KPRI UNM for the five years 2018-2022. Data was obtained from the financial report of KPRI Makassar State University which was analyzed using the calculation formula for economic profitability, own capital profitability, and trend analysis. The research results show that the economic profitability and profitability of the capital owned by KPRI UNM during the five years 2018-2022 are each classified as unhealthy. Trend analysis shows that KPRI UNM during the five years 2018-2022 experienced a tendency to decrease remaining operating results.